Potential Applications of Calocybe indica Ethanol Extract in Noniceptive and Neuronal Pain - De la Cruz, Celia-Vargas; Shariful Islam, Md; Khondokar Abu Raihan, Md.; Jugo, Teresa- Gallardo; Ruiton, César-Fuertes; Ramos-Llica, Eva; GRetuerto Figueroa, Mónica; gutierrez, Arilmi-Gorriti; Gonzalez Elera, Sixto (International Journal of Psychosocial Rehabilitation, 2020)
Calocybe indica belonging to the family Lyophyllaceae, Analgesic potential, CNS test and membrane stabilizing activity of Calocy be indicaethanolicextract (ETCL) were evaluated by some different standard methods. The results of the study showed that ETCI possess peripherally and centrally acting analgesic potential in mice model. In acetic acid induced writhing method, ETCI (100mg/kg & 150mg/kg) significantly (P<0.001, P˂0.05) reduced pain sensation with 71.62% & 54.59% inhibition as compared to standard with 82.96% of inhibition respectively. In hot plate method 100mg/kg ETCI increased reaction time with 13.12%,12.90% &19.40% of latency compare to standard (14.70%, 7.24% & 2.77%) at 0min and 60 min respectively which is statistically significant (p<0.001, P˂0.05). Again ETCI (150mg/kg) increased reaction time (8.19%, 15.09% and 19.79%) which is statistically significant (p<0.001, P˂0.05) at 0min to 60min. In open field method ETCI showed sedative effect (100mg/kg,150mg/kg) at 0min & 60 min which is statistically significant (p<0.001, P˂0.05) but not dose depending manner. In hole cross method ETCI (100mg/kg, 150mg/kg) also showed significant (p<0.001, P˂0.05) sedative effect at 0min & 60 min. The ETCI were effective in membrane stabilizing activity as the extractives prevented the lyses of erythrocytes induced by hypotonic solution. During hypotonic condition the different doses of ETCI (100 &150mg/kg) showed lyses inhibition 65.27% & 10.51% respectively compared to standard with 56.65% of inhibition. The 100mg/kg dose of ETCI had showed the better result than 150mg/kg in membrane stabilizing activity. The investigations revealed that the ethanolic extracts of ETCI possess both central and peripheral analgesic potentials and also have sedative effect with membrane stabilizing activity.